An Analysis of The Voting Behavior of University Students and The Impact of The Presidential Election on The Regional Election in Central Java (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This journal aims to analyze student voting behavior in the context of the 2024 Central Java Gubernatorial Election which is influenced by the dynamics of the 2024 Presidential Election (Pilpres). Using a qualitative approach, this study collects data through in-depth literature research to explore the factors that influence students' voting decisions. The results of the study show that students are greatly influenced by the relevance of national issues raised during the Presidential Election, as well as the quality of policy programs offered by candidates. The use of social media as a means of information and interaction also plays an important role in shaping students' political preferences. In addition, the image and reputation of candidates, as well as the emotional connection of candidates with voters, are significant determinants of students' choices. This study found that the influence of the 2024 Presidential Election on Pilkada creates a complex relationship between national and local political dynamics. These findings are expected to provide insight for regional head candidates and other stakeholders in designing more effective campaign strategies to increase young voter participation in the democratic process.